'Zoals een vriend spreekt met zijn vriend': Jezuïeten uit de Lage Landen en de studie van mystieke theologie - Faesen, Rob (Tijdschrift voor theologie, 2017)
Theology has always been an important focus of the Society of Jesus, right from the foundation of the order in 1540. Yet most specialists agree that there is no such thing as a truly ‘Jesuit theology’, that is to say: a theology with typically Jesuit characteristics. This article discusses the contributions by some Jesuits (mainly from the Low Countries) to the study of mystical theology. They focused on a dimension that features explicitly in Ignatius’ Spiritual Exercises, viz. the idea that God and humans can be intimate and on friendly terms, ‘as one friend speaks to another’ (Spiritual Exercises, 54). Pioneering work was done by Louvain Jesuit Joseph Maréchal – building on older work by Auguste Poulain s.j. – and the studies by his Jesuit companions who later founded the Ruusbroec Institute. Their basic assumption is that mystical texts are not a unique aspect of faith, different from general Christian faith, but that they are testimonies, often in a highly literary form, of a specific (direct and passive) realization of God’s presence. Moreover, some of them (e.g. Albert Deblaere s.j.) have contributed to historical research into the ‘divorce’ between theology and spirituality.